Прогностичка вредност серума SCUBE1, CLEC-2 и UCP2 код акутног исхемијског можданог удара након интравенске тромболизе: Серум SCUBE1, CLEC-2 и UCP2 код акутног исхемијског можданог удара - Sun, Chunying; Liu, Zongmei; Qin, Hongling; Li, Fangcun; Liang, Ni; Gao, Chao; Chen, Wei; Hu, Yueqiang; Zhang, Ding (Journal of Medical Biochemistry, 2025)
Objective: To analyze the predictive value of serum signal peptide-CUB-epidermal growth factor domain-containing protein 1 (SCUBE1), C-type lectin-like receptor-2 (CLEC-2), and uncoupling protein 2 (UCP2) for poor outcome following intravenous thrombolysis (IVT) in patients who have experienced an acute ischemic stroke (AIS).Methods: A total of 116 AIS patients who received IVT treatment in this hospital from June 2023 to October 2024 were selected as the observation group, and the control group consisted of an additional 116 healthy people who were examined physically in this institution over the same time period. The patients were divided into good prognosis and poor prognosis groups according to the modified Rankin scale (mRS) score. After IVT, the factors predicting poor outcome in AIS patients were examined using multivariate logistic regression. The prognostic significance of serum SCUBE1, CLEC-2, and UCP2 for poor prognosis in AIS patients following IVT was examined using a receiver operating characteristic (ROC) curve.Results: While the observation group's serum UCP2 level was lower than the control group's, the observation group's levels of SCUBE1 and CLEC-2 were higher.  P